Uma proposta didática baseada na aprendizagem cooperativa como estratégia metodológica no ensino de termologia utilizando a técnica de investigação em grupo - Silva, Júlio Cesar Santos (2019)
The present work approaches Physics Teaching using Cooperative Learning through the technique “Investigating in group” as a methodological strategy for the teaching-learning process. From this perspective, it was chosen to be worked in a 2nd year high school class at the José de Alencar State School in Fortaleza, the Thermology content, related to the Physics discipline. The main motivating issue for choosing Cooperative Learning as a methodological strategy was to overcome difficulties encountered in the teaching-learning rocess in the context of the discipline of physics. This is evident in the school assessment periods. In this sense, seeking to alleviate the difficulty of students, the choice of this methodology, would facilitate the teaching-learning process by stimulating the interpersonal and cognitive development of students. The present work was developed between February and April of 2019. During this period, for research purposes, we used a control class (TC) and another class chosen to be the experimental class (TE), both with forty-five students. enrolled. The teaching methodology applied in the control class (TC) was in the traditional format, that is, the classes were approached expositively. For the experimental group (TE), the teaching methodology based on ooperative Learning was applied following the Investigating in Group technique approaching Thermology topics. This research made it possible to perform a comparative analysis of the results from a qualitative perspective. The methodology was applied in three stages, namely: pre-implementation, with the planning of activities; implantation, with the accomplishment of the activities and post-implantation, with the analysis of the results. Each step was carefully supervised to identify possible failures and to intervene appropriately if necessary. The results of the study demonstrated an improvement in students' school performance as well as self-esteem and more specifically, fellowship relationships for social and cognitive development.